2019
DOI: 10.1039/c9nr04301b
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in ultra-small fluorescent Au nanoclusters toward oncological research

Abstract: The structure, properties of gold nanoclusters and their applications in targeting anti-cancer fields have been reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 148 publications
0
37
0
Order By: Relevance
“…Recently, Dichiarante et al reported NIR-luminescent AuNCs bearing superfluorinated (SF) ligands with strong emission at 1050 nm with a quantum yield of 12% [77]. An extensive account of the PL of NCs is beyond the scope of this review and has been previously summarized in several reports [54,[78][79][80][81][82]. This review discusses an overview of the application of gold NCs in biosensing and bioimaging.…”
Section: Review Luminescent Gold Nanoclustersmentioning
confidence: 99%
“…Recently, Dichiarante et al reported NIR-luminescent AuNCs bearing superfluorinated (SF) ligands with strong emission at 1050 nm with a quantum yield of 12% [77]. An extensive account of the PL of NCs is beyond the scope of this review and has been previously summarized in several reports [54,[78][79][80][81][82]. This review discusses an overview of the application of gold NCs in biosensing and bioimaging.…”
Section: Review Luminescent Gold Nanoclustersmentioning
confidence: 99%
“…Recent synthetic innovations have allowed the fabrication of atomically precise metal nanoclusters (NCs). [8][9][10][11][12][13][14][15][16][17][18] These metal NCs contain a few to hundreds of metal atoms that are protected by organic ligands (e.g., thiolate, phosphine, small molecules, synthetic polymers, and biomolecules). Particularly, thiolate-protected metal NCs and their alloy NCs can be prepared with atomic precision as M n (SR) m (M ¼ gold (Au), silver (Ag), cupper (Cu), platinum (Pt), palladium (Pd), or other element; SR ¼ thiolate ligand) in a wide range of sizes by varying the n and m values.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned previously, such NCs have potential applications in the elds of energy, environmental science, medicine, and other. [9][10][11][12][13] The M n (SR) m NCs have discrete energy levels due to the quantum size effect, making them signicantly different from the larger (>3 nm) plasmonic metal (Au or Ag) nanoparticles (NPs) with continuous energy levels. By adjusting n and m, one can control the discrete electronic/ geometrical structure of M n (SR) m NCs and thereby their photosensitizing and photo/electrocatalytic capability.…”
Section: Introductionmentioning
confidence: 99%
“…However, the penetration depth of green light is even less than NIR and is thus limited in applicability [39]. Due to their theranostic benefits, such as imaging and biosensing, along with therapeutic properties such as drug delivery, gold nanoclusters have emerged as a useful tool [40,41]. The use of gold nanoclusters can allow for molecular imaging, improving diagnostics and imaging in the future [42].…”
Section: Introductionmentioning
confidence: 99%